Widespread Psammoma Body Formation Arising in the Background of a Uterine Serous Carcinoma. (February 2014) - Salmons, Nabeel Andrew
This report highlights a very rare phenomenon of widespread psammomatous calcification without accompanying epithelium, present in the background of a uterine serous carcinoma. Psammomatous calcification is associated with benign and malignant pathology in different organ systems including the gynaecological tract.